1997
DOI: 10.1183/09031936.97.10081774
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposure to cigarette smoking influences lung function at birth

Abstract: To avoid the possible confounding effects of postnatal exposure to tobacco smoke, we investigated possible effects of uterine tobacco smoke (UTS) exposure upon infant lung function shortly after birth.Infants with no major disease, in one maternity ward in Oslo, Norway, participating in a cohort study established in 1992/1993, were included in the present study (n=803). Exposure information, assessed as maternal active and passive smoking during pregnancy and other personal and environmental factors, was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(105 citation statements)
references
References 26 publications
9
93
2
1
Order By: Relevance
“…Summarising this evidence, three separate studies have shown that babies born to mothers who smoke, or who are atopic, or (interestingly but with no explanation) have hypertension in pregnancy, have abnormal lung function shortly after birth, presumably a reflection of an abnormal intra-uterine process. [19][20][21] Three prospective studies (Tucson, Boston, Perth) showed that in babies with VAW, lung function was abnormal prior to the first episode of wheeze. [22][23][24] Unlike in older children and adults, two studies showed no evidence of bronchial hyper-reactivity in VAW.…”
Section: What Causes Vaw?mentioning
confidence: 99%
“…Summarising this evidence, three separate studies have shown that babies born to mothers who smoke, or who are atopic, or (interestingly but with no explanation) have hypertension in pregnancy, have abnormal lung function shortly after birth, presumably a reflection of an abnormal intra-uterine process. [19][20][21] Three prospective studies (Tucson, Boston, Perth) showed that in babies with VAW, lung function was abnormal prior to the first episode of wheeze. [22][23][24] Unlike in older children and adults, two studies showed no evidence of bronchial hyper-reactivity in VAW.…”
Section: What Causes Vaw?mentioning
confidence: 99%
“…Studies with various PAHs in rodent models have clearly shown that certain PAH cause not only teratogeneis, but also at elevated risk of cancer (59)(60)(61)(62). Studies have also clearly shown also that exposure to environmental carcinogens and the resulting effect on the developing offspring is a time-dependent phenomena, with specific gestational times being more clearly susceptible to the effects of carcinogenic compounds than other times (63)(64)(65)(66)(67)(68). As a result, exposure to carcinogenic PAH at early stages of pregnancy and fetal development has a much greater impact than late term exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies using tidal breathing indices of lung function, 14,15 and one using the squeeze technique to produce partial flow volume curves 16 have clearly demonstrated that infants have abnormal lung function very soon after birth; risk factors include a maternal history of atopy, maternal smoking and (interestingly and quite unexplained) maternal hypertension during the pregnancy. One group has suggested on the basis of complex physiological measurements that it may be abnormal airway wall compliance rather than calibre which is important in virus associated wheeze.…”
Section: Specific Categories Of Coughmentioning
confidence: 99%